A facile approach to construct BiOI/Bi5O7I composites with heterostructures: efficient charge separation and enhanced photocatalytic activity1. Issue 91 (9th October 2015) - Yu, Yaoguang; Chen, Gang; Wang, Xu; Jia, Dechang; Tang, Pengxiao; Lv, Chade
<x xml:space="preserve">Abstract</x> A series of BiOI/Bi5O7I composite photocatalysts with heterostructures was successfully synthetized through a facile hydrothermal method.